2014
DOI: 10.1111/cbdd.12442
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Pharmacological Evaluation of Novel NO‐Releasing Benzimidazole Hybrids as Potential Antihypertensive Candidate

Abstract: Two series of novel NO-releasing benzimidazole derivatives (8a-e, 9a-g) were designed and synthesized by coupling nitro ester and furoxan NO-donor moieties with benzimidazole biphenyl skeleton. The NO-releasing assay indicated that all the target compounds had different level of NO-releasing ability. Furthermore, the isolated organ assay (rat aortic strips) was used to evaluate the antagonism of Ang II-induced vasoconstriction ability. It was observed that the pA2 values of compounds 8e and 9e were better than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used. This result suggested that NO-releasing benzimidazole hybrids may provide a promising approach for the discovery of 23 . Benzimidazole derivatives were recently reviewed as target agents for antidiabetic by different mechanisms such as peroxisome proliferator-activated receptor á-transcriptional activity, glycosidases receptor, dipeptidyl peptidase IV, glucokinase, human glucagon receptor (hGCGR) antagonist, aldose reductase enzyme and stearoyl-CoA desaturase 24 .…”
Section: -9mentioning
confidence: 92%
“…The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used. This result suggested that NO-releasing benzimidazole hybrids may provide a promising approach for the discovery of 23 . Benzimidazole derivatives were recently reviewed as target agents for antidiabetic by different mechanisms such as peroxisome proliferator-activated receptor á-transcriptional activity, glycosidases receptor, dipeptidyl peptidase IV, glucokinase, human glucagon receptor (hGCGR) antagonist, aldose reductase enzyme and stearoyl-CoA desaturase 24 .…”
Section: -9mentioning
confidence: 92%
“…Two series of nitric oxide (NO) releasing benzimidazole derivatives were synthesized by coupling benzimidazole biphenyl skeleton with nitro ester and furoxan NO-donor moieties, where compounds 393–394 were reported to possess comparable activity to positive control losartan ( Zhang et al, 2015 ). Hao et al ( Hao et al, 2015 ) designed and synthesized a series of 4′-[(benzimidazol-1-yl)methyl]biphenyl-2-sulphonamide derivatives and reported that compound 395 was found to be the most potent AT 1 and Endothelin ET A receptor antagonist with IC 50 values 28 and 10 nM, respectively.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…4 Accordingly, it is worthy to develop new medicinal compounds possessing appreciable antioxidant activity for the management of microbial infections. Benzimidazoles and coumarins are reported as antibmicrobial 5 , antiviral 6 , antidiabetic 7,8 , antihypertensive 9,10 , antitumor 11 , and antioxidants 12,13 . In light of the literature, it looked worthful that a combination of benzimidazole moiety and coumarin moiety may provide medicinal compounds that possess appreciable antioxidant activity as well as antimicrobial potential.…”
Section: Introductionmentioning
confidence: 99%